The effect and correlation of pack years of smoking on the hematological parameters, lipid profile and coagulation profile: A case control study - Samarth Rastogi; Kanika Singh; Mukta Pujani; Varsha Chauhan; Charu Agarwal; Kamal Gera (Al Ameen Medical College, 2021)
Introduction: Cigarette smoking is considered a major risk factor for atherosclerosis, coronary heart disease, stroke and cancer. Objectives: To compare the Complete Blood Count, Lipid Profile and Coagulation profile (PT, aPTT) in the smokers and non-smokers and to study the correlation of pack years of smoking with the above parameters. Methodology: The study was a case control study (110 smokers as cases and 110 non smokers as controls). The cases were grouped into mild smokers (<5 pack years), moderate smokers (5-10 pack years) and heavy smokers (>10 pack years).A complete blood count including Differential leucocyte count, Lipid Profile and Coagulation profile was done. Observation and Results: The RBC count and TLC were significantly elevated, however, MCV and MCH were significantly reduced in the smokers with a p value <.05. The S. cholesterol and LDL values were raised in the smokers (168.58±39.95 versus 157.71±35.94) and (103.92±35.01 versus 93.86±29.76) respectively. A significant difference was found in the TLC, S. cholesterol and S. Triglyceride values among the mild, moderate and severe smokers with p values 0.023, 0.022, 0.014 respectively. A significant positive correlation of pack years of smoking with TLC, S. Cholesterol, S. triglyceride and a PTT was also noted with correlation coefficients 0.320 ( p = 0.023) ,0.21( p=0.027), 0.230(0.015) and 0.379 (p= 0.0004) respectively. Conclusion:A significantly increased RBC count and TLC, however reduced MCV and MCH was noted in smokers. Also the smokers were associated with a significant positive correlation of S. Chol, S. TG with increasing pack years of smoking. The coagulation profile (aPTT) was also affected in the smokers with a strong positive correlation with increasing pack years of smoking. Thus the monitoring of the hematological parameters like TLC, RBC and lipid profile (S. Chol and S.TG) and aPTT would help in early intervention and thus reducing the morbidity and mortality due to smoking.